ASSA13-14-3 Iron Metabolism Disorder in Hypopxia-Induced Pulmonary Hypertension Rats. (29th April 2013) - Ying, Li; Xiaohui, Li; Hong, Yuan
Abstract : Background and Objective: Iron supplement is efficient to inhibit the increase of pulmonary arterial systolic pressure (PASP) induced by hypoxia. And recently, iron deficiency is normally observed in idiopathic pulmonary arterial hypertension (IPAH) patients, while the situation of iron metabolism and its regulatory mechanism under hypoxic pulmonary hypertension (HPH) is seldom known. The aim of this study is to observe the existence of iron metabolism disorder and discuss the possible mechanism in HPH rat. Methods: HPH rats was induced by 4-weeks hypoxia. Beside blood regular test, blood samples were collected for determination of several factors related to iron metabolism including iron, ferritin, transferritin and hepcidin, which is synthesised in liver and plays a key role in inhibiting iron absorption, release and storage. Furthermore, RNA and protein were extracted from liver tissues to evaluate the transcriptional level of hepcidin and protein expression of the upstream regulator of hepcidin, BMP6. Results: Iron concentration (12.5 ± 2.41 vs 5.78 ± 2.86. P = 0.033) was significantly decreased in HPH rats, while the plasma level of transferritin (1.6 ± 0.59 vs 5.78 ± 2.86. P = 0.012) and hepcidin (1.6 ± 0.59 vs 5.78 ± 2.86. P = 0.048) were increased. Plasma level of ferritin was also decreased but the change is not significant (1.6 ± 0.59 vs 5.78 ± 2.86. P = 0.051). WBC (1.6 ± 0.59 vs 5.78 ± 2.86. P = 0.013) and MCV (57.58 ± 2.39 vs 61.28 ± 2.01, P = 0.029) were decreased in HPH rats showed from blood regular test. Q-PCR and western blot experiments showed that hepcidin mRNA level and BMP6 protein level were both significantly increased in liver. Conlusions: Disorder of iron metabolism generally exists in HPH rats and an up-regulated BMP6/hepcidin signalling pathway in liver may contribute to this progress.